ANALISA PERBANDINGAN TINGKAT EFISIENSI ALGORITMA DATA DEFINITION LANGUAGE COPY, INPLACE, INSTANT DATABASE MYSQL - Sinata, Frans (Universitas Bunda Mulia, 2023)
MySQL database schema changes are becoming more frequent than ever, Four out of five application updates (releases) require appropriate database changes, For Database schema changes are more often a repetitive task, it may be a request from the application team to add or modify a column in a table and many cases other. This study aims to measure the level of time efficiency to modify the sales transaction table schema which consists of 50000 number of records in the MySQL database with the Data Definition Language (DDL) Copy, Inplace and Instant algorithm on the MySQL database.